2003
DOI: 10.1080/1360786021000045863
|View full text |Cite
|
Sign up to set email alerts
|

An electronic memory aid to support prospective memory in patients in the early stages of Alzheimer's disease: A pilot study

Abstract: The use of an electronic memory aid (EMA) for patients with mild-to-moderate probable Alzheimer disease is examined in five outpatients aged 58-79 years. The ability to remember to carry out seven tasks at a particular time was evaluated in three experimental conditions: recall without an external memory aid, recall with a written list and recall with support available from an EMA. The use of an EMA significantly improved patients' prospective memory, while the written list and free recall were not useful. Fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 26 publications
1
38
0
1
Order By: Relevance
“…Future studies might also examine the association between qualitative aspects of ProM performance and neurovirologic (e.g., biomarkers of macrophage activation), neuroimaging, and neuropathologic variables in HIV-1 infection. Also, the present findings are not specific to HIV-infection, nor to conditions with fronto-striatal systems disruption, since ProM deficits are evident in numerous neurologic conditions (e.g., Alzheimer's disease; Oriani et al, 2003).…”
Section: Discussionmentioning
confidence: 93%
“…Future studies might also examine the association between qualitative aspects of ProM performance and neurovirologic (e.g., biomarkers of macrophage activation), neuroimaging, and neuropathologic variables in HIV-1 infection. Also, the present findings are not specific to HIV-infection, nor to conditions with fronto-striatal systems disruption, since ProM deficits are evident in numerous neurologic conditions (e.g., Alzheimer's disease; Oriani et al, 2003).…”
Section: Discussionmentioning
confidence: 93%
“…Several case series and very small comparative studies with less than 20 participants have suggested that this approach may have some potential clinical utility, particularly for promoting improved functioning. [37][38][39] Although the evidence base is preliminary, this approach appears to be initially valid and is simple and practical to implement.…”
Section: Memory Aidsmentioning
confidence: 99%
“…Ob sich die Einsetzbarkeit der Geräte bessert, wenn in Zukunft eine Generation von Demenzpatienten heranwächst, die über langjäh-rige Erfahrung (d. h. prozedurales Wissen) bei der Bedienung von Handys und Palms verfügen werden, bleibt abzuwarten. Während zum Einsatz elektronischer Gedächtnishilfen bei nichtprogressiver Amnesie bereits replizierte Wirksamkeitsnachweise vorliegen, existiert für Alzheimer-Patienten bisher nur eine Einzelfallstudie [35], bei der 4 Patienten mit leichter Gedächtnisstörung bei der Bearbeitung prospektiver Gedächtnisaufgaben vom Gebrauch einer elektronischen Gedächt-nishilfe mehr profitierten konnten als von einer geschriebenen Liste. Da es sich bei den Tätigkeiten um artifizielle, vom Versuchsleiter vorgegebene Handlungen im klinischen Setting handelte (z.…”
Section: Externe Gedächtnishilfenunclassified